Challenges in Food Safety as Part of Food Security: Lessons Learnt on Food Safety in a Globalized World. (2016) - Uyttendaele, Mieke; De Boeck, Elien; Jacxsens, Liesbeth
Abstract: Food safety should accomplish food and nutrition security. A key challenge to scale up food safety globally is to better leverage existing capacity and research working towards evidence-based decisions. At Ghent University since 2009 an annual 3-months international Intensive Training Program on Food Safety, Quality Assurance and Risk Analysis has been organized (www.itpfoodsafety.UGent.be ). The trainees were asked to express their opinion on food safety concerns in their country and to select a case study to work on throughout the course. Main food safety issues had to do with bacterial pathogens, pesticide residues and mycotoxins which were challenged by lack of food safety knowledge and appropriate legislation and enforcement by government. They welcomed education and training on these topics in particular to elaborate on control measures including good hygienic practices, implementation of certified food safety management systems and setting of appropriate criteria. A number of topics are highlighted here in particular as these topics were shown to have a common ground of interest by several participants in several countries and throughout the years. These topics include among others safety of street foods, safe milk and cheese production, and risk assessment to control Salmonella and pathogenic E. coli in meat (and other foods). Although some recurring food safety issues could be identified, other topics are of particular concern in selected countries because of specific cultural appropriate eating habits. The world is changing fast. Problems change and the information stream is very intense. Leaders in food security should be aware about food safety as well, and will have to develop an attitude of continuous learning, critical thinking and be given the right tools("know how") to develop local solutions to address the emerging societal and environmental challenges to provide sufficient, safe, healthy, nutritious and sustainable produced food to the world's population.